Peran Pendidikan dalam Pembentukan Kesadaran Kesetaraan Gender pada Remaja - Warasanto, Untung Arif; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to explore the contribution of education in building understanding of gender equality among adolescents. Understanding gender is a crucial element in social development that affects how individuals perceive roles and interactions within society. Education serves as a strategic arena that forms the basis for shaping social values and norms without gender bias. The method used in this study is descriptive qualitative with a literature review approach, which evaluates various sources such as academic journals and relevant policy documents. The research findings indicate that understanding of gender can be internalized through intramural, co-curricular, and extracurricular activities, each focusing on the cognitive, affective, and practical actions of students. This approach has the potential to change students' attitudes and behaviors regarding gender equality, while also creating a fair and inclusive educational environment. The study recommends enhancing teacher capabilities, fostering community collaboration, and developing gender-responsive evaluation tools as further steps to support the sustainability of education programs on gender equality.